2004
DOI: 10.1080/00288233.2004.9513619
|View full text |Cite
|
Sign up to set email alerts
|

Control of gaseous emissions of ammonia and hydrogen sulphide from cow manure by use of natural materials

Abstract: Winter management practices involving the use of stand-off pads to reduce problems due to cows grazing on wet soils may require storage of cow manure for extended periods prior to field application. Gaseous losses of nitrogen (N) and sulphur (S) from stored cow manure can be considerable, and these gases are offensive and undesirable. Laboratory incubation studies were conducted to measure gaseous loss of ammonia (NH 3 ) and hydrogen sulphide (H 2 S) from stored cow manure under aerobic and anaerobic condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As the stocking rate was three cows per hectare on this grazed pasture, the stand‐off pad itself could contribute about 0.01 kg N 2 O‐N per hectare of grazed pasture to the total emissions associated with the whole farm system. The immobilization of cow excreta N in the wood materials in the pad because of the high C/N ratios of pine bark and sawdust (Luo et al. , 2004) probably caused the initial very low N 2 O emission rates when the cows started to use the pad.…”
Section: Resultsmentioning
confidence: 99%
“…As the stocking rate was three cows per hectare on this grazed pasture, the stand‐off pad itself could contribute about 0.01 kg N 2 O‐N per hectare of grazed pasture to the total emissions associated with the whole farm system. The immobilization of cow excreta N in the wood materials in the pad because of the high C/N ratios of pine bark and sawdust (Luo et al. , 2004) probably caused the initial very low N 2 O emission rates when the cows started to use the pad.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, delaying FDE-irrigation after a grazing event could further reduce N 2 O emissions by reducing the levels of surplus mineral-N. However, gaseous emissions from FDE during storage need to be controlled (Luo et al 2004a).…”
Section: Strategy For Reducing N 2 O Emissionsmentioning
confidence: 99%
“…Ammonium ions, either hydrolysed or mineralised from cows' excreta, can adsorb onto cation exchange surfaces, therefore decreasing the quantity of dissolved ammonium ions and the quantity of equilibrated NH 3 gas available for ammonia volatilisation. This was demonstrated by lower NH 3 volatilisation losses from bark-and sawdust-amended cow manure than unamended manure (Luo et al 2004). Sorption of odorous compounds, including NH 3 gas, by pine bark has also been found to be one of the important mechanisms in removal of odours by biofilters containing bark .…”
Section: Nitrogen In Stand-off Pads and Drainagementioning
confidence: 99%
“…There are literature reports of the effectiveness of some materials with potential for use in stand-off pads (Bolan et al 2004;Luo et al 2004;Misselbrook & Powell 2005;Vinten et al 2006;Luo & Saggar 2008). in a study in which cow manure was mixed with pine bark, it was found that the bark retained N and reduced gaseous losses including ammonia (NH 3 ) and hydrogen sulphide (H 2 S) (Luo et al 2004). These workers considered that the retention of N may have been due to adsorption and/or immobilisation of N and sulphur by the C-rich bark.…”
Section: Introductionmentioning
confidence: 99%